Factors Predicting Disease Control in Patients with Asthma, Banphaeo General Hospital, Samut Sakhon - Junphongsri, Pruegsa; Wattanakitkrileart, Doungrut; Phligbua, Warunee; Dejsomritrutai, Wanchai (Nursing Science Journal of Thailand, 2024)
Purpose: This study aimed to examine the predictive power of body mass index (BMI), comorbidity (hypertension, gastroesophageal reflux disease, or GERD), sleep quality, and trigger avoidance behavior on disease control in patients with asthma. Design: Predictive correlational research. Methods: The sample consisted of 139 patients with asthma, aged 20 years and older, who had been admitted to the lung clinic of Banphaeo General Hospital in Samut Sakhon Province. Convenience sampling was used to select those having normal cognition, no other type of lung disease, no psychiatric disorder, and no comorbidities with severe symptoms. Data were collected by using personal data questionnaire and an asthma control assessment form based on Global Initiative for Asthma (GINA) criteria, the Pittsburgh Sleep Quality Index, the GERD-Q Questionnaire, and a questionnaire on trigger avoidance behavior. The data were analyzed by employing descriptive statistics and logistic regression. Main findings: The results revealed that 74.8% of the respondents were female, with a mean age of 60.41 years (SD = 13.9), and 59% had good control of asthma. BMI, GERD, and sleep quality were associated with asthma control ( 2 = 17.19, p < .01; 2 = 9.09, p < .01; 2 = 4.83, p = .028, respectively). The analysis of predictive power showed that BMI (OR = 9.98, 95%CI [2.76, 36.08], p < .001), GERD (OR = 2.78, 95%CI [1.25, 6.21], p = .012), and sleep quality (OR = 2.53, 95%CI [1.03, 6.18], p = .042) were able to significantly predict asthma control in patients. Conclusion and recommendations: BMI, GERD, and sleep quality were predictors of asthma control. The findings recommend that nurses should promote the control of body weight and GERD and improve sleep quality for better asthma control.